Investigation of Drying Time and Final Moisture Content of Arabica beans in a Solar Drying Chamber - Rendi Ramdhani; Selly Septianissa; Ahmad Rajani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Drying is a critical stage that affect directly the quality, storability, and market value of Arabica coffee beans. The objective of this study was to investigate the performance of a solar drying chamber integrated with a thermal collector and phase change material (PCM), operated under a constant airflow velocity of 9.2 m/s. Arabica beans of 1500 g were dried over two observation days, with chamber temperatures ranging from 40 °C to 46.5 °C and peak solar radiation of 1122 W/m². The results showed that the system effectively maintained thermal stability and drying performance despite fluctuations in solar input. The analysis revealed at Day 2 achieved a higher and faster moisture reduction due to improved solar conditions and absorber efficiency, with drying rates peaking at over 42 g vapor per hour in the third hour. In contrast, at Day 1 the drying rate peaked in the third hour at approximately 22.45 g vapor/h. Day 1 exhibited a more stable but slower drying trend. Overall, the system successfully reduced the beans’ moisture content to below 12.8% in within under 14 hours, with Tray 2 delivering the most consistent results. These findings demonstrate that the integration of solar thermal energy, PCM, and forced convection application significantly improved drying efficiency and reliability, offering a sustainable alternative for post-harvest processing, especially in regions with variable weather conditions.